The Impacts of Free Cash Flow and Agency Cost on Firm Performance - Muadz Rizki Muzakki; Imo Gandakusuma (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to examine the effect of free cash flow and agency cost to firm performance. The purpose of this study to provide empirically evidence about the effect of free cash flow and agency cost to firm performance. This study also examines the free cash flow hypothesis developed by Jensen (1986). Recent study about this topic resulting mixed/various result. Free cash flow in this study measured by free cash flow t-1, agency cost proxied by operating expenses ratio. Firm performance divided into three, operational performance measured by ROA, firm value measured by tobin's q ratio, and share return measured by holding period return. This study will conduct on manufacturing companies listed on Indonesian Stock Exchange period of 2017-2021. Sample were selected by purposive random sampling method and finally obtained 396 samples that fulfill the criteria. Data were analyzed using multiple regression analysis. The result show that free cash flow has insignificant positive effect on firm operational performance, firm value and share return. Agency cost has significant negative effect on firm operational performance, firm value and share return. This study provides empirical evidence of the effect agency cost on firm performance and provides contribution to the literature on free cash flow hypothesis topics